Psychiatrie. (2020) - Granger, Bernard; Rouditch-Pergola, Oleg; Lambert, Dorian; Cristofini, Grégoire; Radoykov, Stéphane; Ladarré, Anne; Dutaillis, Camille; Nafa, Hana; Santiago, Antoine; Dutemple, Margaux; Leroux-Auger, Raphaëlle; Jaffré, Claire; et al.
No abstract available